Information Technology and Organizational Learning : Managing Behavioral Change in the Digital Age - Langer, Arthur M. (Boca Raton, FL : CRC Press, 2017)
"Focusing on the critical role IT plays in organizational development, the book shows how to employ action learning to improve the competitiveness of an organization. Defining the current IT problem from an operational and strategic perspective, it presents a collection of case studies that illustrate key learning issues. It details a dynamic model for effective IT management through adaptive learning techniques-supplying proven educational theories and practices to foster the required changes in your staff. It examines existing organizational learning theories and the historical problems that occurred with companies that have used them, as well as those that have failed to use them. "--Provided by publisher.
chapter 1 The (3z(BRavell(3y (BCorporation -- chapter 2 The IT Dilemma -- chapter 3 Technology as a Variable and Responsive Organizational Dynamism -- chapter 4 Organizational Learning Theories and Technology -- chapter 5 Managing Organizational Learning and Technology -- chapter 6 Organizational Transformation and the Balanced Scorecard -- chapter 7 Virtual Teams and Outsourcing -- chapter 8 Synergistic Union of IT and Organizational Learning -- chapter 9 Forming a Cyber Security Culture -- chapter 10 Digital Transformation and Changes in Consumer Behavior -- chapter 11 Integrating Generation Y Employees to Accelerate Competitive Advantage -- chapter 12 Toward Best Practices -- chapter 13 conclusIons.s
Keywords: Organizational learning; Information technology -- Management; Business, Management and Accounting; BUSINESSnetBASE/MANAGEMENTnetBASE; Engineering Management; ENGnetBASE; GENERALENGINEERINGnetBASE; INFORMATIONSCIENCEnetBASE; ITECHnetBASE; Management of IT; SCI-TECHnetBASE; STMnetBASE